Structural-based Study to Identify the Repurposed Candidates against Bacterial Infections - Dey, Debanjan; Kumar, Anoop (Current Medicinal Chemistry, 2025)
BackgroundMicrobial infections are mostly caused by Gram-positive as well as Gram-negative bacteria affecting millions of people worldwide. There is an urgent need to explore existing molecules or discover new chemical entities (NCEs) against bacterial infection.ObjectiveThe main objective of the current investigation is to explore recently US-FDA-approved drugs (2019-2023) against various targets of Gram-positive and Gram-negative bacteria using high-performance computational studies.AimThe current study aims to find out the potential drugs of recently US-FDA-approved drugs as repurposing candidates against bacterial infections.MethodsThe targets of Gram-positive and Gram-negative bacteria were identified using literature studies whereas ligands were selected from the FDA-approved drug lists of the last 5 years. Further, the drugs and targets were prepared through the LigPrep and Protein Preparation Wizard modules of Schrödinger (release 2023-1) respectively. The GlideDock and Desmond modules of Schrödinger were used for the molecular docking study and molecular dynamics simulation respectively.ResultsA total of 202 drugs were found in the FDA lists which were approved in the last five years. Out of them, 77 drugs were selected for docking study based on their properties. A total of 21 drugs have shown energetically favored binding conformation of drugs in the active site of bacterial targets. The interaction of these drugs was studied in detail using molecular dynamics (MD) simulation. The MD simulation results have shown stable dynamic conformation of triclabendazole (anti-helminthic) with topoisomerase II of gram-negative bacteria whereas solriamfetol (for obstructive sleep apnea) has shown stable dynamic conformation in the active site of restriction endonuclease of Gram-positive bacteria.ConclusionThe identified drugs can be repurposed against Gram-positive and Gram-negative bacterial infections. However, further experimental studies are required to confirm their antibacterial potential.
Keywords: molecular dynamics